EHV-1 Pathogenesis: Current in vitro Models and Future Perspectives - Kamel, Mohamed; Pavulraj, Selvaraj; Osterrieder, Klaus; Azab, Walid (Frontiers in Veterinary Science, 2019)
Primary infection and pathogenesis of equine herpesvirus type 1 (EHV-1) require an intricate interaction of virus with the mucosal epithelium, mononuclear cells and the vascular endothelium. Studies on EHV-1 have been facilitated by the development of different in vitro models that recapitulate the in vivo tissue complexity. The available in vitro assays can be categorized into (i) models mimicking the epithelium-peripheral blood mononuclear cell (PBMC) interaction, which include ex vivo mucosal (nasal and vaginal) explants and equine respiratory epithelial cells (EREC) cultures; and (ii) PBMC-endothelium mimicking models, including flow chamber and contact assays. These in vitro models have proven their worth in attempts to recapitulate the in vivo architecture and complexity, produce data relevant to natural host infection, and reduce animal use due to in vivo experiments. Although horse models are still needed for certain experiments, e.g. EHV-1 myeloencephalopathy or vaccination studies, available in vitro models can be used to obtain highly valuable data on virus-host tissue interactions. Microfluidic based 3D culture system (e.g., horse-on-a-chip) could be a potential upgraded version of these in vitro models for future research.